Class-E RF power amplifier with a digitally-controlled output matching network for dynamic load modulation - Liu, Qianqian (2018)
This Master of Engineering research project pertains to the analysis, design, and Integrated Circuit (IC) realization of a novel Class-E RF Power Amplifier (PA) capable of generating a variable-envelope output signal for Polar transmitters in Wireless Body Area Network (WBAN) with emphasis on high power efficiencies. A Class-E RF PA with a novel digitally-controlled variable output matching network (OMN) is proposed. The PA is designed so that the ZVS condition can be achieved for high-efficiency operation. The OMN performs the Dynamic Load Modulation (DLM), and is controlled/varied directly by the digital Amplitude Modulation (AM) input signal without any need for a conventional supply modulator, thereby saving area and power dissipation. The OMN architecture design allows the use of on-chip inductors, as well as off-chip inductors including high Quality factor bond-wires to improve the efficiency. The proposed Class-E PA embodying the novel digitally-controlled variable OMN is designed using the TSMC CMOS 40 nm technology and benchmarked, based on the IEEE 802.15.6 standard for WBAN, against a reference state-of-the-art PA. The benchmarking shows that the proposed PA features a higher drain efficiency, while achieving a similar/comparable performance to that of the reference PA.